A call to spy [videorecording (DVD)] - Thomas, Sarah Megan, 1979-; Thomas, Sarah Megan, 1979-; Katic, Stana; Apte, Radhika; Roache, Linus, 1964- (Shout! Factory, 2021)
At the beginning of WWII, with Britain becoming desperate, Churchill orders his new spy agency, SOE, to recruit and train women as spies.